Blue hydrogen must be done properly. Issue 9 (23rd June 2022) - Pettersen, Jostein; Steeneveldt, Rosetta; Grainger, David; Scott, Tyler; Holst, Louise‐Marie; Hamborg, Espen Steinseth
Abstract: Future energy scenarios include both green and blue hydrogen, as both are needed to scale up decarbonized energy supply. A transition to renewable energy is predicted over time, but the urgency we are facing cannot be met by renewable energy alone. For blue hydrogen production, the overall greenhouse gas (GHG) emissions are primarily affected by emissions from natural gas production, processing, and transport (CO2 and methane), as well as process efficiency and carbon capture ratio. Few complete and updated analyses are available that cover the entire blue hydrogen value chain with the best available technology for process facilities, as well as the proper design, operation, and maintenance of all relevant systems and infrastructure. This paper analyses the GHG intensity of blue hydrogen, using recent data as well as input from technology providers on state‐of‐the‐art gas reforming technologies. Data are primarily based on natural gas production and transport in the North Sea Basin, with gas export from the Norwegian continental shelf to continental Europe or the United Kingdom, and with blue hydrogen production either in Norway or near pipeline landfall in the European Union or United Kingdom. Some data related to potential blue hydrogen production in the US Appalachian region are also given. The data show that the properly designed and operated value chains for blue hydrogen supply, with minimal emissions from natural gas supply and high carbon capture in hydrogen production, will give a major reduction in GHG emissions from energy end‐use. GHG footprint for end‐users based on blue hydrogen will typically be 80%–90% lower than for direct supply and use of natural gas. Abstract : When done properly, blue hydrogen is a credible option for decarbonization of energy end‐use. More than 80% reduction in greenhouse gas (GHG) emissions is typically achieved compared to direct supply and use of natural gas. GHG intensity of supplied hydrogen range from 0.6 to 2 kg CO2 e per kg hydrogen. GHG intensity depends on gas supply, carbon capture ratio of reformer, and GHG intensity of consumed electricity.